2009
DOI: 10.1080/10826080902960007
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Needs of Men and Women with Violence Problems In Substance Use Disorder Treatment

Abstract: This study examined treatment needs of men and women in Substance Use Disorder treatment. The sample (n = 489) was recruited between 2006 and 2007 from a Midwestern state in the US, and participants were grouped based on injury occurring in partner and non-partner relationships in the past year. Rates of injury across relationship types were alarming with over 54.8% reporting injuring another person and 55.4% reporting being injured. Overall, those injuring non-partners or both partners/non-partners had more s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 78 publications
8
45
0
5
Order By: Relevance
“…To our knowledge, it is the first study to examine the correlates of both anger and violence in the one sample and to assess for the influence of comorbid disorders and trait aggression. The demographic characteristics of the sample are consistent with other samples of individuals entering substance use treatment (Burnette et al, 2008;Chermack et al, 2009;Mills et al, 2005).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…To our knowledge, it is the first study to examine the correlates of both anger and violence in the one sample and to assess for the influence of comorbid disorders and trait aggression. The demographic characteristics of the sample are consistent with other samples of individuals entering substance use treatment (Burnette et al, 2008;Chermack et al, 2009;Mills et al, 2005).…”
Section: Discussionmentioning
confidence: 50%
“…For instance, Walton, Chermack, and Blow (2002) found that individuals reporting more severe levels of psychological distress during treatment were most likely to continue to express violence post-treatment. Research has also emerged that suggests symptoms of depression play a role in the perpetration of violence among individuals with SUD (Chermack et al, 2009;Murray et al, 2008).…”
Section: Anger Among Individuals With Sudmentioning
confidence: 97%
“…Next, several studies have shown that history of childhood physical and sexual abuse is related to a higher risk of substance use disorders, criminal behaviour and antisocial personality traits in adults (Warren & South, 2006;Holovits et al, 2009;Kimonis et al, 2010;Shin et al, 2010). There is evidence that individuals showing both partner and non-partner aggressive behaviours have greater levels of clinical problem severity (higher levels of psychiatric distress, depression, substance use and antisocial traits) Chermack et al, 2009) and that non-partner aggression is associated with more demographic factors compared with partner aggression (Chermack et al, 2001). Finally, previous non-ED studies also highlight the importance of social support as a protective factor or coping strategy for violent victimization (Coker et al, 2002;McWhirter, 2010;Reid-Quinones et al, 2011;Wong et al, 2011); however, the role of social support in terms of protective factor for aggressive behaviour has been studied only recently and has not been evaluated among ED patients (Brookmeyer et al, 2011).…”
Section: Introductionmentioning
confidence: 93%
“…childhood abuse history, antisocial traits, alcohol intoxication, drug problems and social support) of aggressive behaviour between participants reporting partner aggression or non-partner aggression compared with those reporting no aggression. Based on prior research, it was hypothesized that male gender would be associated with more involvement in non-partner violence only Chermack et al, 2009), whereas female gender would be more associated with partner violence (Lipsky et al, 2004;Walton et al, 2009) and that younger age would be associated with aggressive behaviour in both partner and non-partner aggressive groups (Lipsky et al, 2004;McCloskey et al, 2005;Cunningham et al, 2009;Walton et al, 2009). In terms of other clinical correlates, we expected antisocial traits, childhood abuse history, alcohol intoxication and drug use disorders would be positively associated with aggression with partners and non-partners Chermack et al, 2009).…”
Section: Goals Of the This Studymentioning
confidence: 99%
“…The personal and social costs of aggressive behavior are tremendous and include physical and emotional injuries, relationship and legal problems, lower social functioning and higher utilization of health care services (Campbell, 2002;Marshall, Panuzio, & Taft, 2005). In addition, aggressive behavior has been linked to poorer SUD treatment outcomes (e.g., higher drop-out, earlier relapse; Gossop, Trakada, Stewart, & Witton, 2005;Mignone, Klostermann, & Chen, 2009;Murphy & Ting, 2010;Ravndal & Vaglum, 1991), which suggests the need for integrated interventions (Chermack et al, 2009;Fals-Stewart & Kennedy, 2005;Klostermann, Kelley, Mignone, Pusateri, & Fals-Stewart, 2010).…”
Section: Introductionmentioning
confidence: 98%